Optimizing nutrients intake of children in Indonesia: Dietary modelling approach - Sunardi, Diana; Wibowo, Yulianti (Indonesian Nutrition Association, 2024)
The prevalence of obesity is rising in high-income countries, while low-income populations face the triple burden of malnutrition. Improving dietary intake is crucial in addressing these issues. Diet optimization or diet modelling have emerged as valuable tools for identifying the optimal combination of foods that meet daily nutritional requirements by incorporating nutrient-dense options into the diet.